Միջազգային մարդասիրական իրավունքի խախտումներն Ադրբեջանի կողմից Արցախի մշակութային արժեքների ռազմականացման դեպքում - Տիգրանյան, Արմինե Հ․
2020 թ. 44-օրյա պատերազմի ընթացքում և դրանից հետո Արցախի մի շարք եկեղեցիներ, համայնքային մշակութային ու կրթական կենտրոններ Ադրբեջանը սկսեց օգտագործել ռազմական նպատակով՝ խաթարելով վերջիններիս մշակութային գործառույթը։ During and after the 2020 war, a number of churches, community-based cultural centers, and educational institutions in Artsakh were repurposed by Azerbaijan for military objectives, undermining their cultural functions. The article aims to study the international legal framework governing the use of cultural heritage for military purposes during armed conflicts, with a particular focus on International Humanitarian Law. It seeks to examine specific cases of Azerbaijani forces using Armenian monuments in Artsakh for military purposes from 2020 to 2024. Во время и после 44-дневной войны 2020 года ряд церквей, культурных и об-разовательных центров общин Арцаха были использованы Азербайджаном в военных целях, что подорвало их культурную функцию. Цель статьи: Статья рассматривает конкретные случаи использования азербайджанскими силами армянских памятников Арцаха в военных целях в период с 2020 по 2024 годы.
Keywords: Պատմություն